Can Fetuin A Be Utilized in the Evaluation of Elderly Patients with Acute Myocardial Infarction? - Raluca Tomoaia (Life, 2021)
Background: Lower baseline Fetuin-A (FA) is associated with left ventricular remodeling and cardiovascular death (CVD) at 4 months after acute myocardial infarction (AMI). However, the association between FA levels, incomplete ST segment resolution (STR) following primary percutaneous coronary intervention (PCI) and early mortality in AMI has not been previously studied. Methods: We enrolled 100 patients with AMI, which we divided in two groups: 21 patients who suffered sudden cardiac death (SCD) in the first 7 days after PCI and 79 controls. We measured FA, NT-proBNP and troponin levels and correlated them with the occurrence of death in the first week after revascularization. We also tested the cut-off value of FA to determine STR at 90 min after PCI. Results: SCD was most frequently caused by pump failure (n = 10, 47.6%) and ventricular arrhythmias (n = 9, 42.5%). Plasma FA levels correlated with NT-proBNP values (r = −0.47, p = 0.04) and were significantly lower in patients presenting SCD (115 (95–175) vs. 180 (105–250) ng/mL, p = 0.03). Among all three biomarkers, FA was the only one associated with incomplete STR after PCI on the multivariate logistic regression (cut-off value of 175 ng/mL, Se = 74%, Sp = 61.1%). Death rate was highest (n = 16/55, 30%) in patients with FA levels below the cut-off value of 175 ng/mL. Conclusion: Lower FA is associated with higher early mortality and incomplete STR after primary percutaneous revascularization in patients with AMI. Measurement of FA levels in addition to NT-proBNP, troponin and STR might enable more accurate identification of high-risk patients.